A case study on application of ORESTE for agile concept selection. Issue 4 (3rd October 2016) - Arjun Raj, A.S.; Vinodh, Sekar
Abstract : Purpose: The purpose of this paper is to report a research on application of ORESTE (Organization, Rangement Et Synthese De Donnees Relationnelles, when translated into English means organization, storage and summarizing data relational) for agile concept selection. Design/methodology/approach: The concept selection problem has been formulated as a multi-criteria decision-making (MCDM) problem to select the best concept design of the rotary switch component. ORESTE has been used as solution methodology. The selected concept design alternatives were subjected to implementation. Findings: As ORESTE is a preferential outranking method, it uses ordinal data, enabling decision makers in situations where practically sufficient data are not available. This paper uses ORESTE for agile concept selection where gathering sufficient data is difficult. Also, the results generated by ORESTE have been compared with technique for order performance by similarity to an ideal solution. Research limitations/implications: In the present study, ORESTE has been applied for concept selection of rotary switch component. In future, more number of studies need to be conducted to select more concept design alternatives where getting prior information is difficult or consumes more time to ensure practical effectiveness of ORESTE. Practical implications: The application of ORESTE for concept design selection enabled the practitioners to select the best concept with ordinal data and also enabled scope for indifferentiability and incomparableness of any two alternatives in the final outranking. Originality/value: Formulation of MCDM problem for agile concept selection and solution generation using ORESTE is the original contribution of the authors.